2021
DOI: 10.1002/ange.202006988
|View full text |Cite
|
Sign up to set email alerts
|

Übergangsmetallkomplexe als Katalysatoren für die elektrische Umwandlung von CO2 – eine metallorganische Perspektive

Abstract: Die elektrokatalytische Umwandlung von Kohlendioxid ist in der CO2‐Nutzung seit langem von Interesse. Während sich viele Studien auf den direkten Elektronentransfer vom Elektrodenmaterial auf das CO2‐Molekül konzentrieren, bieten molekulare Übergangsmetallkomplexe in Lösung die Möglichkeit, als Katalysatoren für den Elektronentransfer zu wirken. C1‐Verbindungen wie Kohlenmonoxid, Formiat oder Methanol werden oft als Hauptprodukte angestrebt, aber auch kompliziertere Umwandlungen sind innerhalb der Koordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 566 publications
(279 reference statements)
0
2
0
Order By: Relevance
“…9,10 On the other hand, homogeneous metal complexes are essential systems for studying CO 2 RR mechanisms at a molecular level, offering superior selectivity and exceptional activity. [11][12][13] Wang and co-workers found that homogeneous catalysts were actually dynamically adsorbed on the electrode surface in a homogeneous system. 14 These metal complexes allow for precise tailoring of well-defined active site structures.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 On the other hand, homogeneous metal complexes are essential systems for studying CO 2 RR mechanisms at a molecular level, offering superior selectivity and exceptional activity. [11][12][13] Wang and co-workers found that homogeneous catalysts were actually dynamically adsorbed on the electrode surface in a homogeneous system. 14 These metal complexes allow for precise tailoring of well-defined active site structures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The conversion of CO2 to value-added products, as part of a carbon neutral (or negative) cycle, is an attractive strategy for addressing the challenges associated with the rising atmospheric CO2 concentration. [4][5][6][7][8][9] The electrocatalytic reduction of CO2 to CO could significantly alter the emissions impact of industrial processes related to Fischer-Tropsch chemistry and syngas, if hydrogen from renewable sources is used. [10][11][12][13] The reduction of CO2 to CO by molecular electrocatalysts requires the sequential transfer of two electrons and an oxo acceptor (e.g.…”
mentioning
confidence: 99%